The political feasibility of adjustment in Ecuador and Venezuela - De Janvry, Alain; Organisation for Economic Co-operation and Development. Development Centre (Paris Organisation for Economic Co-operation and Development, 1994)
"Political feasibility of adjustment / Christian Morrison, general editor."
Keywords: Structural adjustment (Economic policy) -- Ecuador; Structural adjustment (Economic policy) -- Venezuela; Ecuador -- Economic policy; Venezuela -- Economic policy